Processing word prosody—behavioral and neuroimaging evidence for heterogeneous performance in a language with variable stress - Heisterueber, Miriam; Klein, Elise; Willmes, Klaus; Heim, Stefan; Domahs, Frank (Frontiers in Psychology, 2014)
In the present behavioral and fMRI study, we investigated for the first time interindividual variability in word stress processing in a language with variable stress position (German) in order to identify behavioral predictors and neural correlates underlying these differences. It has been argued that speakers of languages with variable stress should perform relatively well in tasks tapping into the representation and processing of word stress, given that this is a relevant feature of their language. Nevertheless, in previous studies on word stress processing large degrees of interindividual variability have been observed but were ignored or left unexplained. Twenty-five native speakers of German performed a sequence recall task using both segmental and suprasegmental stimuli. In general, the suprasegmental condition activated a subcortico-cortico-cerebellar network including, amongst others, bilateral inferior frontal gyrus, insula, precuneus, cerebellum, the basal ganglia, pre-SMA and SMA, which has been suggested to be dedicated to the processing of temporal aspects of speech. However, substantial interindividual differences were observed. In particular, main effects of group were observed in the left middle temporal gyrus (below vs. above average performance in stress processing) and in the left precuneus (above vs. below average). Moreover, condition (segmental vs. suprasegmental) and group (above vs. below average) interacted in the right hippocampus and cerebellum. At the behavioral level, differences in word stress processing could be partly explained by individual performance in basic auditory perception including duration discrimination and by working memory performance (WM). We conclude that even in a language with variable stress, interindividual differences in behavioral performance and in the neuro-cognitive foundations of stress processing can be observed which may partly be traced back to individual basic auditory processing and WM performance.